Penerapan Terapi Aktivitas Kelompok (TAK) Terhadap Penurunan Tingkat Halusinasi Pendengaran Pada Pasien Skizofernia Di RSJD Dr. RM Soedjarwadi Klaten - Evika Nadinar Anjani; Wahyu Reknoningsih; Siti Rahma Soleman (Jurnal Ventilator, 2023)
Background: Schizophrenia is a common health problem worldwide, around 70% of people suffering from schizophrenia experience auditory hallucinations. Auditory hallucinations are where patients feel that they can hear voices without a sound source. This situation causes the patient's inability to perceive reality accurately. One of the nursing interventions performed for auditory hallucinations is perceptual stimulation group activity therapy. Method: The method used in this application is descriptive with a case study research design, research subjects totaling 2 respondents, sheet research instruments observation that is AHRS . Findings: There were differences in scores before and after being given Group Activity Therapy (TAK), namely a decrease in the hallucination level score on Mr. F and Mr. W. Implication: Based on the results of the study, it was found that there was an effect of Group Activity Therapy (TAK) in controlling auditory hallucinations in schizophrenic patients after being given Group Activity Therapy (TAK) for 2 applications. In addition to providing Group Activity Therapy (TAK), the patient's recovery or stability is also supported by continued treatment and rehabilitation.